Holy war: history of an idea - Ruelland, Jacques G. (Mellen Press, 2007)
War and holy war -- Holy war and sacred war -- The Hebrews and holy war -- The weapons of Yahweh -- From holy war to just war -- The Islamic Jihad -- The Crusades -- The notion of indulgence -- The concept of purgatory -- Chronology of the Crusades -- The Byzantine Pseudo-Crusades -- The wars of religion -- The suicidal tactics of the Germans and the Japanese -- Redefining peace -- The notions and relationships of holy war